Static Mixers for Water Ozonation: Applications and MathematicalModelling - A Review - Mohamed A. M. Saad, Abdullah. A. Elamari, Awad. E. Alshebani, E. M. Elmabrouk, Sana Ibrahim Abukanisha (Journal of Pure & Applied Sciences, 2020)
Static mixers have been successfully employed in water and wastewater treatment, particularly in water ozonation for disinfection and oxidation purposes. Producing higher concentration of ozone requires new contactors that operate efficiently at low gas/liquid ratio. The Kenics static mixer can meet these requirements and therefore enhance the ozone mass transfer rate. This paper summarises the field of static mixers in water ozonation including comparison with other gas/liquid contactors. This study also reviews recent conceptual and technological innovations in static mixers: Current industrial applications, advantages and types are discussed, focusing on mixing and mass transfer performance. The work is complemented by a review of mixing fundamentals, knowledge of which allows the development of mathematical models which are crucial for the analysis of experimental data. Moreover, it reviews the recent advances of the mathematical models of zone mass transfer in static mixer: back flow cell model (BFCM), Axial diffusion model (ADM) and the continuous flow stirred tanks in series (CFSTR’s in series). Both the steady state and the transient BFCMs were validated with experimental data by Tizaoui and Zhang and it was found that they accurately predicted the outlet ozone concentration and the impulse RTD curves of gas-liquid system respectively along height of the static mixer.